Global labelling for sustainable development - Piñeiro, Valeria; Elverdin, Pablo; Pascuzzi, Nieves; de Oliveira, Susan Elizabeth Martins Cesar (T20 Brazil, 2024)
Food production is a complex and varied set of activities, both agricultural and nonagricultural, involving an increasing number of sectors and actors that influence the way food is produced, processed, distributed, and consumed. Also new dimensions are being considered when food is produced, traded, and exported. The impact of agrifood systems on the environment and the wellbeing of farmers stand out, as well as concerns about the safety and nutritional quality of food. Over the last decades, economic growth together with urbanization, social, and culinary changes resulted in a shift toward more unhealthier diets. Specially, the increased consumption of ultra processed food has led to a higher incidence of overweight and obesity. Faced with this concern, many governments have made progress in the design and implementation of policies to promote healthier diets. Mandatory labeling of processed products is rapidly growing, but its legislation varies in each country, causing confusion among consumers and affecting food SMEs' access to third markets. International trade is essential for food security and nutrition. Given that more than one-fifth of all food consumed worldwide is imported, evidencing the global interdependence of agrifood systems, it requires countries to work together. The G20 countries have the ability to take the initiative to advance greater harmonization.